The Study of the Optimal Route for Waste Collection by Using Vehicle Routing Problem in Chulachomklao Royal Military Academy - พลตื้อธนะกูล วิชญ์ชพล (วารสารวิชาการ โรงเรียนนายร้อยพระจุลจอมเกล้า, 2023)
The waste problem in Chulachomklao Royal Military Academy has been continually increasing and affecting the environment as well as the quality of life of the personnel. Waste disposal is becoming increasingly difficult due to changing consumption and now requires more energy. Currently, the Transportation Section of the Support Division Chulachomklao Royal Military Academy must collect solid waste from all 45 government offices and residences for disposal in the landfills at the Prommanee Sub-district Administration Organization of Nakhon Nayok Province. The support of waste trucks is also lacking in terms of equipment rates due to the limited number of waste trucks, so waste collection needs to be properly managed in terms of transportation planning. Based on these problems, the objective of this research is to find the most optimal route for waste collection by applying a mathematical model for the Vehicle Routing Problem (VRP), Heuristic Principles including Cluster-First Route-Second method and Sweep Heuristic method. Then compare it with traditional transportation to find the shortest route and provide guidelines for resource-efficient waste collection planning. The study concluded that the Cluster First Route Second+ VRP 2 Group method has the shortest transportation distance, which can reduce the transportation distance from the original 110.71 kilometers to the total transportation distance of 75.66 kilometers and reduce the transportation cost by 1,525.09 baht per week or 31.66 percent of the original transportation costs.